2022
DOI: 10.3389/ti.2021.10036
|View full text |Cite
|
Sign up to set email alerts
|

Adult Combined Heart-Liver Transplantation: The United States Experience

Abstract: Background: We aimed to review the indications and outcomes of adults undergoing combined heart-liver transplantation (CHLT) in the US using national registry data.Methods: Adult (≥18 years) CHLT recipients in the United Network for Organ Sharing database were included (09/1987–09/2020; era 1 = 1989–2000, era 2 = 2001–2010, era 3 = 2011–2020). Survival analysis was conducted by means of Kaplan-Meier method, log-rank test, and Cox regression.Results: We identified 369 adults receiving CHLT between 12/1989–08/20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Both single-center studies and analyses of large databases have demonstrated favorable outcomes after SHLT. [110][111][112][113] In an SRTR analysis, survival of SHLT at 1, 3, and 5 years was 86.8%, 82.8%, and 81.3%, respectively. 111 In a UNOS registry analysis, survival after SHLT was comparable to that after HT alone.…”
Section: Heart-liver Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Both single-center studies and analyses of large databases have demonstrated favorable outcomes after SHLT. [110][111][112][113] In an SRTR analysis, survival of SHLT at 1, 3, and 5 years was 86.8%, 82.8%, and 81.3%, respectively. 111 In a UNOS registry analysis, survival after SHLT was comparable to that after HT alone.…”
Section: Heart-liver Transplantationmentioning
confidence: 99%
“…[110][111][112][113] In an SRTR analysis, survival of SHLT at 1, 3, and 5 years was 86.8%, 82.8%, and 81.3%, respectively. 111 In a UNOS registry analysis, survival after SHLT was comparable to that after HT alone. 114…”
Section: Heart-liver Transplantationmentioning
confidence: 99%
“…Further multivariate analysis demonstrated that recipient diabetes and a sequential liver-first approach were independently associated with an increased risk of mortality [6 ▪ ]. Higher donor left ventricular ejection fraction was associated with decreased risk of mortality.…”
Section: Discussionmentioning
confidence: 91%
“…Studies analyzing UNOS registry data through 2020 describe the current, national landscape of CHLT with improvement in patient survival over time [6 ▪ ,23,24]. Analysis of 364 recipients who underwent CHLT shows overall survival of 86.8, 80.1, and 77.9% at 1, 3, and 5 years, respectively [6 ▪ ]. Although indications for CHLT have changed over time with a predominance of congenital heart disease in the modern era, interestingly, there was no difference in survival when stratified by cardiac diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…[4,7] Subsequently, CHD patients, which originally represented 17%-50% of all CHLTs from 2009 to 2017, have increased to 95% CHLTs in 2019, whereas other indications, such as nonischemic cardiomyopathy and amyloidosis-related cardiomyopathy, have decreased in frequency. [7] A subject of intense debate in the transplant community is the decision of which patients with CHD and liver disease benefit from CHLT compared with HT. [8] Uncertainties surrounding the diagnosis of cirrhosis and portal hypertension in CHD patients make listing decisions complicated.…”
Section: Introductionmentioning
confidence: 99%